การจัดการศึกษาทางไกลผ่านดาวเทียมของโรงเรียนขนาดเล็กในยุคการศึกษาไทย 4.0 - หมั่นดี, นิดา; หฤทัยธนาสันติ์, ธีร (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 29 No 2 (2561): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2018.38, 2018)
การจัดการศึกษาทางไกลผ่านดาวเทียมเป็นนโยบายหนึ่งที่รัฐบาลดำเนินการเพื่อแก้ไขปัญหาขาดแคลนครูของโรงเรียนขนาดเล็กและเพิ่มโอกาสในการเข้าถึงการศึกษาที่ทันสมัยของนักเรียนในชนบทของประเทศไทย และเมื่อเข้าสู่ไทยแลนด์ 4.0 ที่เป็นการขับเคลื่อนประเทศด้วยนวัตกรรม การจัดการศึกษาทางไกลผ่านดาวเทียมของโรงเรียนขนาดเล็กก็ต้องมีการพัฒนารูปแบบและวิธีการเพื่อให้รองรับการเข้าสู่ยุคการศึกษาไทย 4.0 ด้วยเช่นกัน บทความวิชาการฉบับนี้นำเสนอการจัดการศึกษาทางไกลผ่านดาวเทียมที่ผ่านมา การศึกษาไทย 4.0 ทฤษฎีและแนวคิดสู่การจัดการศึกษาทางไกลผ่านดาวเทียมในยุคการศึกษาไทย 4.0 และปัญหา ข้อจำกัด และแนวทางขับเคลื่อนโรงเรียนขนาดเล็กสู่การจัดการศึกษาทางไกลผ่านดาวเทียมในยุคการศึกษาไทย 4.0 เพื่อเป็นแนวทางในการยกระดับคุณภาพของโรงเรียนขนาดเล็กต่อไป คำสำคัญ: การจัดการศึกษา, การศึกษาทางไกล, ดาวเทียม, โรงเรียนขนาดเล็ก, การศึกษาไทย 4.0   Educational management of Distance Learning Television (DLTV) is a policy that resolving the lack of teachers of small-sized schools and increasing access to quality education for rural students in Thailand. In the age of Thailand 4.0 with the aim to develop the country with innovations, the educational management of distance learning television of small-sized schools have been required to develop its models and methods in order to support Thai education 4.0. This article is offered the past educational management of distance learning television, Thai education 4.0, theories and concept for educational management of distance learning television in Thai education 4.0 and problems, limitations and guidelines driving small-sized schools to educational management of distance learning television in Thai education 4.0, these are guidelines to raise the quality of small-sized schools. Keywords: educational management, Distance Learning Television (DLTV), distance learning education, small-sized school, Thai education 4.0